Are Maternal Education, Maternal Occupation, and Breastfeeding Escalate Nutrition Status in Stunted Children? - Sari, Ria Setia; Ratnasari, Febi; Susilowati, Yuni (Masters Program in Public Health, Universitas Sebelas Maret, Indonesia, 2021)
Background: Stunting is a nutritional problem that has a negative impact on achieving optimal growth and development in children. The Tangerang District Health Office has a high percentage of stunting children. Improving the nutrition of stunting children is influenced by providing balanced nutrition to children. Stunting children have an old orange with elementary-high school education. This study aims to determine the relationship between mother's education, mother's occupation and exclusive breastfeeding with the improvement of nutritional status in stunting children. Subjects and Method: This research was conducted using cross sectional with a total sample of 45 subjects. The dependent variable is the improvement of stunting nutritional status. The independent variables were the mother's education level, occupation and exclusive breastfeeding status. Data was collected using a questionnaire. Data were analyzed using multiple logistic regression test. Results: Low education affects the improvement of nutritional status in children (aOR= 1.68; 95% CI= 0.53 to 5.31; p= 0.660), Employment as a protective factor on nutritional status in stunted children (aOR= 0.64; 95% CI= 0.16 to 2.87; p = 0.450) Conclusion: Mother's education affects the improvement of nutritional status in stunted children.